ANALISA STATISTIK DEBIT BANJIR DAN DEBIT ANDALAN SUNGAI KOMERING SUMATERA SELATAN - Redaksi Tim Jurnal (Sekolah Tinggi Teknik - PLN, 2017)
River flow discharge is one of the most important hydrological parameters for the management of water resources because river flow data is required for future pusposes assuming the process characteristics are unchanged. Komering River is one of the largest rivers in the Province South Sumatra which is quite a big role in the lives of people who are in the sub Komering watershed. The magnitude of the flood discharge and dependable flow Komering River is very important to to be taken into account, by analyzing the flood discharge can be done flood management, while by analyzing the dependable flow can be done planning river water utilization. The research based on the collection of secondary data obtained from Departemen Pekerjaan Umum Sumatera Selatan and Balai Besar Wilayah Sungai Sumatera VIII, discharge data from 2000 to 2010 and maps needed to know the study area. All the data are correlated where the analysis is intended to determine the statistics of flood discharge and dependable flow Komering River. From the results of analyzes obtained that the distribution can be used to predict flooding in the river discharge is Gumbel distribution with estimate the flood discharge for 2 years return period 1007.57 m³/dt, for 5 years return period 1459.79 m³/dt, for 10 years return period 1759.20 m³/dt, for 25 years return peiod 2137.50 m³/dt, for 50 years return period 2418.15 m³/dt, and for 100 years return period 2696.73 m³/dt. Based on analysis of dependable flow, Month Basic Plan Method, thatLog Pearson III distribution can be used to analyze River Komering dependable flow. The highest dependable flow of is 226.20 m³/dt and the lowest dependable flow is 62.08 m³/dt.